IDENTITY POLITICS AND RELIGIOUS PROPAGANDA IN THE 2023 NIGERIA'S GENERAL ELECTIONS: A CALL FOR SOCIAL PEACE - Alimi Quadri Olamilekan (A Priori, 2025)
It is not a gainsaying that 2023 general elections in Nigeria do not only leave a political scar in the mind of many Nigerians but also an everlasting hallmark in the political system and nation building. As some Nigerians count their political gains; others also count their political loss, hence this has widened the level of disintegration in the process of nation building and loss of patriotism among Nigerians. In the history of election in Nigeria, the past election is one of the most contested since 1999 when the country returned to democratic system. The political atmosphere was intensified riding on the factors of identity politics and religious propaganda among the citizens. It is unfortunate that past administration does not meet the high expectation of the masses which was believed as the better choice of party to brings dividends of democracy to the people after the failure of former political party that has clinched to power for almost two decades. However, with another grievous disappointment; some Nigerians, majorly the youths sought for credible candidate as flagbearer of another political party to determine the path to the new Nigeria which has been clamouring for since independence. This brought a three-man race election polarized on accusation and counter-accusation on ethnic sensitivity and religious identities between the Northern and Southern Nigeria. The paper examines the influence of identity politics and religious propaganda on the development of electoral system in Nigeria. It adopted qualitative method using secondary sources and empirical studies to evaluate the position of ethno-religious identity in Nigeria’s political system. The study discovered that the nation is more ethnically divided and disintegrated among some ethnic groups especially Nigerian youths because of the results of elections. The paper makes recommendations on adopting most suitable applicable and practicable system of government that would respect and recognize ethno-religious identities, eliminate marginalization and equal representation in Nigeria political system.